Production of laying hens in different rearing systems under hot weather (Acta Scientiarum. Animal Sciences, 2017)
The environment is very important for the performance of laying hens; thus, techniques are required to improve production systems, providing better welfare for poultry and consequent increase in the quality of the final product, the egg. This study aimed to evaluate the effects of rearing system, on the floor and in cage, on the performance and egg internal and external quality of laying hens. A total of 320 Hysex Brown laying hens, with 34-43 weeks days of age, was distributed in a completely randomized design, with two treatments, floor and cage, with 10 replicates each. The parameters evaluated were: individual feed intake, egg production per replicate, feed conversion per dozen eggs, egg weight; weight and percentage participation of shell, albumen and yolk, specific gravity, body weight variation and viability of birds. The results show that the birds raised on the floor showed best results as to egg production, besides the best internal and external quality, with greater weight of egg, yolk, albumen, shell and with lower losses of eggs. Because of the negative effects of the cage system, in general, hens presented lower results when compared to results of those raised on the floor.